Fenomena Keberadaan Kaum Marginal dalam Masyarakat: Sebuah Kajian Literatur Standpoint Theory - Kinanthi Fatwasuci; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This paper examines how standpoint theory is used in various research studies based on communication theory. The standpoint theory proposed by Sandra Harding focuses on how the marginalized power, which is no greater than the dominant, is placed in society. This theory clarifies the point of view that differences in equality between people can be presents in gender, sexual orientation, race, or ethnicity. Scientific writing uses a qualitative approach with the use of literature review methods, the methods which focuses on previous research in the past five years (starting from 2021).